Enhancing crop productivity, profitability and input use efficiency through efficient crop diversification in Bangladesh: comparing diversified cropping patterns in Dinajpur, Bangladesh - Washiq, Faisal; Hossain, Akbar; Aonti, Annika Jahan; Md. Mobinur Rahman; Gathala, Mahesh Kumar; Cheesman, Stephanie; Alanuzzaman Kurishi, A.S.M.; Krupnik, Timothy J. (TAFSSA, 2024)
In recent times, the sustainability of rice-rice cropping systems has been threatened by yield plateaus, high input costs, declining water and labor availability, and increasing food demand. Hence, rice-based cropping systems require more attention to ensure future food security. This research note summarizes the impact of crop diversification on crop and water productivity, yield, and profitability based on data from an agronomic research platform trial conducted over one complete cropping cycle. The trial was established at the Bangladesh Wheat and Maize Research Institute (BWMRI) in Dinajpur, Bangladesh, in August 2022.